Influence of physical methods of pre-sowing treatment on seed germination of some medicinal plants - Amenova, D.M.; Ageev, D.V.; Tolesh, A.; Seldiugaev, O.B.; Zinovev, L.A.; Nortseva, M.A. (Fundamental and Experimental Biology, 2022)
The use of physical processing methods improves the viability of seeds of many species of cultivated plants. Physical processing methods are more environmentally friendly, cheap,can be easily implemented when organizing collection sites and plantations. The use of physical methods of pre-sowing seed treatment of medicinal plants has not previously been carried out. The article presents the results of studying the effects of physical methods (magnetic field irradiation and bubbling), on the germination rate and energy of germination of the seeds of Salvia stepposa, Linum usitatissimum, Valeriana officinalisafter 1,5 years of storage. The results demostrated that the viability of the seeds of all three species was significantlyincreased compared to the control after irradiation with a magnetic field and the use of bubbling for 24 hours. The best physical method of presowing treatment for Salvia stepposaseeds was recognized as the combination of cryopreservation and bubbling, for Linum usitatissimum andValeriana officinalisseeds were irradiation with a double magnetic field for 3 days.